One-step electrospinning PCL/ph-LPSQ nanofibrous membrane with excellent self-cleaning and oil-water separation performance. (17th May 2022) - Wang, Faqiang; Liu, Kexin; Xi, Yanni; Li, Zhanxiong
Abstract: The ladder-like phenyl polysilsesquioxane (ph-LPSQ) was synthesized by sol-gel method. Then the Polycaprolactone/ladder-like polysilsesquioxane (PCL/ph-LPSQ) nanofibrous membranes were prepared via one-step electrospinning technique. The addition of ph-LPSQ was proposed to improve the hydrophobic and thermal properties of PCL membranes. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) images showed the PCL/ph-LPSQ composite fibers had porous rough surface structure, which was caused by solvent evaporation induced phase separation, respiration diagram and silicon segment migration. The composition of PCL/ph-LPSQ membranes was characterized by using fourier transform infrared spectroscopy (FT-IR), x-ray photoelectron spectroscopy (XPS) and energy dispersive x-ray spectroscopy (EDS). Compared with pristine PCL membranes, the water contact angle and initial degradation temperature for PCL/ph-LPSQ membranes were increased to 158.0° and 355 °C, respectively, from the corresponding 133.6° and 340 °C. The superhydrophobic PCL/ph-LPSQ membranes exhibited excellent self-cleaning, anti-fouling and oil-water separation performance. Driven by gravity alone, the oil-water separation efficiency remained as high as 98% after ten cycles. More importantly, the as-prepared membrane showed good stability in 80 °C, 1 M acid, alkali and salt solutions. Considering the comprehensive properties of PCL/ph-LPSQ membranes, it might be a promising nonwoven fabric material in many fields like textile manufacturing industry. Graphical abstract: Image 1 Highlights: A facile and ingenious method of preparing super hydrophobic nanofibrous membrane was developed in this paper. The thermal and hydrophobic properties of the composite membrane were improved with the addition of organo-silicon polymer. The as-prepared membranes exhibited excellent self-cleaning and oil-water separation performance.